2004
DOI: 10.1002/gps.1032
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine versus placebo in the treatment of psychosis with or without associated behavioral disturbances in patients with Alzheimer's disease

Abstract: While 1.0 mg olanzapine did not show significant differences from placebo, the 2.5 mg dose was a reasonable starting dose. Olanzapine at 7.5 mg/day significantly decreased psychosis and overall behavioral disturbances (NPI/NH, BPRS) and was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
2
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(143 citation statements)
references
References 47 publications
3
132
2
6
Order By: Relevance
“…The effectiveness of antipsychotic medication for psychosis, agitation and aggression in dementia has been demonstrated in some studies (Brodaty et al, 2003;Cummings et al, 2002;De Deyn et al, 2004), but the results are contradictory as other studies have reported no effect of antipsychotic medication for NPS (Schneider et al, 2006). In reviews and meta-analyses the effect of atypical antipsychotic medication was demonstrated for risperidone (reducing aggression and psychosis) and aripiprazol (reducing aggression and psychosis), but the effect of the medication has to be balanced by the side effects of the medication (Ballard and Corbett, 2010).…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…The effectiveness of antipsychotic medication for psychosis, agitation and aggression in dementia has been demonstrated in some studies (Brodaty et al, 2003;Cummings et al, 2002;De Deyn et al, 2004), but the results are contradictory as other studies have reported no effect of antipsychotic medication for NPS (Schneider et al, 2006). In reviews and meta-analyses the effect of atypical antipsychotic medication was demonstrated for risperidone (reducing aggression and psychosis) and aripiprazol (reducing aggression and psychosis), but the effect of the medication has to be balanced by the side effects of the medication (Ballard and Corbett, 2010).…”
Section: Antipsychotic Medicationmentioning
confidence: 99%
“…8 This deterioration may, however, be explained by sedation 9 or the lower baseline cognition in the quetiapine group. 10 Studies of the atypical olanzapine have reported mixed results, ranging from no effect 11 to enhancing 12 or worsening cognition. 13 RCTs using risperidone for neuropsychiatric symptoms in dementia have, however, consistently found it to be effective without cognitive side effects.…”
mentioning
confidence: 99%
“…Foram identificados nove ECR controlados com placebo, sendo quatro estudos com risperidona (De Deyn et al, 1999;Katz et al, 1999;Brodaty et al, 2003;Mintzer et al, 2006), dois com olanzapina (Street et al, 2000;De Deyn et al, 2004), um com risperidona e olanzapina (Debert et al, 2005), um com quetiapina (Ballard et al, 2005) e um com aripiprazol (De Deyn et al, 2005). Todos os ECR identificados foram incluídos nas metanálises, e suas características estão descritas na Tabela 1.…”
Section: Resultsunclassified
“…De Deyn et al (2004) avaliaram a eficácia de doses fixas de olanzapina (1; 2,5; 5 ou 7,5mg/dia) no tratamento de sintomas psicóticos de 652 idosos durante dez semanas. Não houve diferença entre os grupos olanzapina e placebo.…”
Section: Olanzapinaunclassified